Analysis of Quality in Public and Private Universities in Bangladesh and USA - Quamrul H Mazumder (International Journal of Evaluation and Research in Education (IJERE), 2014)
To meet the growing need for increased capacity in higher education, the government of Bangladesh encouraged development of private universities in 1992.  Currently, there are sixty private universities1, thirty-four public universities2 and  three international universities in Bangladesh3.  Although the increased number of universities has provided opportunities, a debate has emerged over the quality at these institutions due to significant difference among these institutions.  These inconsistencies in quality may be due to the lack of regulatory oversight and inefficiencies of the regulatory agencies of the government.  The cost of education at private universities is high compared to significantly lower cost at public universities that are subsidized by the government.  In spite of the higher cost, student satisfaction levels have not been higher at private universities in the past4.  The work presented in this paper seeks to determine the quality of education in public and private universities in Bangladesh using student satisfaction as a measure of quality.  It is well understood that student satisfaction measure may not be the only indicator of quality, but it can be considered as one of the important indicators.   The survey questions were modified to adapt them to the context of Bangladesh.   The twenty-two question survey results from private and public university students of Bangladesh were compared to determine the level of student satisfaction.  The results of the current study were compared with the SSI data of US private and public universities.  Results of the current study  showed that the students in public universities of Bangladesh had lowest level of satisfaction and the private universities of Bangladesh had highest satisfaction The results derived from this data can be used by both public and private universities for improving quality in higher education.DOI: http://dx.doi.org/10.11591/ijere.v3i2.2886